Inadecuada contemplación de las medidas cautelares alternativas, por contravenir el principio constitucional de seguridad jurídica en el código de procedimiento penal. - SILVA BUSTAMANTE, LUIS ALBERTO (2011)
The Penal Right and their Juridical different Figures, to say of the current tendencies of the penology ones, they constitute the source of the aspects or principles of the punitive Right that are essential in the juridical structure. legal of the State, in what to the structure of process prison the specialists present in the matter. The importance and transcendency of the juridical outlined problem, on the inadequate view of the alternative precautionary measures, to contravene the constitutional principle of Artificial Security, in the Code of Penal Procedure, I want to refer that that the sovereign town of Ecuador, approved in the Popular Consultation of May of the 2011 where, the posteriority of the case in question, deserves the intervention of the legislature, same that incorporated the alternative measures, now they even have a responsibility bigger, but it consists the question with respect to the precautionary measures on what, this made necessary the study that verifies the legal adaptation of a normative one to punish this motive and the penal type, in the national legislation, by means of you even sanction of more rigurosidad with the novel intervention of this modus operandi. The theoretical Content and the empiric investigation in the development of the artificial investigation, contain the budgets fácticos that allowed to define the contribution of the verification of the proposed objectives and the foundation of the proposal accurately, with the support of the literary bibliography that you/they cooperated to the formulated changes, as important source of a serious and appropriate study. This work of scientific investigation, I present it as a budget that he/she is born of the intellectual effort where guidelines of character scientist appear and methodological that interprets the investigation in their group, on the formula of adapting in the Penal Code, a disposition that sanctions the computer science's indiscriminate use in the fraud against the crimes against the property that allows to minimize this mean of criminal participation, in people of their authors, accomplices and concealing.